THE EFFECTIVENESS OF LITERACY TEACHING MATERIALS BASED ON LOCAL WISDOM IN IMPROVING LITERACY SKILLS FOR ELEMENTARY SCHOOL STUDENTS - Ifah Hanifah; Muchlas Suseno; Miftahulkhairah Anwar (Universitas Galuh, 2022)
Teaching materials are a factor that can determine success in achieving a particular skill. Therefore, in improving students' literacy skills, teaching materials are needed as support. So, a study was conducted under the title